Titania Thin Films: Key Factors for Template‐Oriented Porous Titania Synthesis: Solvents and Catalysts (Small Methods 3/2020). Issue 3 (6th March 2020) - Yin, Shanshan; Song, Lin; Xia, Senlin; Cheng, Yajun; Hohn, Nuri; Chen, Wei; Wang, Kun; Cao, Wei; Hou, Shujin; Müller‐Buschbaum, Peter
Abstract : In article number 1900689, Peter Müller‐Buschbaum and co‐workers explore the effect of solvent category and hydrochloric acid content on the morphologies of amphiphilic diblock copolymer (PS‐b‐PEO)‐templated titanium dioxide thin films. Spherical, laminar, cylindrical, and saccate nanostructures consisting of an anatase crystalline titanium dioxide phase are obtained through simple component regulation of the sol–gel stock solution.